2017
DOI: 10.18632/oncotarget.21043
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol induces autophagic cell death of hepatocellular carcinoma cells via activating AMPK signaling

Abstract: In the present study, we demonstrate that Kaempferol inhibited survival and proliferation of established human hepatocellular carcinoma (HCC) cell lines (HepG2, Huh-7, BEL7402, and SMMC) and primary human HCC cells. Kaempferol treatment in HCC cells induced profound AMP-activated protein kinase (AMPK) activation, which led to Ulk1 phosphorylation, mTOR complex 1 inhibition and cell autophagy. Autophagy induction was reflected by Beclin-1/autophagy gene 5 upregulation and p62 degradation as well as light chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…The role of autophagy in promoting cell survival or inducing cell death during the development of HCC is still controversial [10]. Some previous studies showed that autophagy could promote HCC cell survival in response to environmental stresses [18,31], while other studies reported that autophagy induced HCC cell death [32,33]. Therefore, whether autophagy promotes cell survival or induces cell death depends on the cell type and environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…The role of autophagy in promoting cell survival or inducing cell death during the development of HCC is still controversial [10]. Some previous studies showed that autophagy could promote HCC cell survival in response to environmental stresses [18,31], while other studies reported that autophagy induced HCC cell death [32,33]. Therefore, whether autophagy promotes cell survival or induces cell death depends on the cell type and environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…We refer the reader to a thorough review that has highlighted many studies showing ADCD by various agents in different cancer cell types, such as the BH3 mimetics obatoclax and gossypol, histone deacetylase inhibitors, as well as the natural plant products resveratrol and betulinic acid (Fulda and Kögel, 2015). Additionally, more recent studies that have clearly demonstrated autophagy gene-dependent cell death in the absence of apoptosis include the treatment of glioma cells with a combination of the tricyclic antidepressant imipramine (IM) and the anti-platelet drug ticlopidine (TIC; an inhibitor of ADP receptor P2Y 12 ) (Shchors et al, 2015), the treatment of lung carcinoma cells with cabazitaxel (Huo et al, 2016) and the treatment of hepatocellular carcinoma with the natural flavonoid kaempferol (Han et al, 2017). Importantly, ADCD triggered by IM and TIC has also been associated with slower tumor progression and improved survival in in vivo mouse glioma models; knockdown of Atg7 in the glioma cells attenuates the effects of the drugs on survival and tumor growth (Shchors et al, 2015).…”
Section: Adcd In Pathophysiological Conditionsmentioning
confidence: 99%
“…2). The first mechanism involves changes in the regulatory steps that affect autophagy induction, either through modulation of the Vps34-Beclin-1 complex (see below and Box 1; note Vps34 is also known as the class III PI3K or PIK3C3 in mammals), or by activation of AMP-activated protein kinase (AMPK), which has multiple targets within the autophagy initiation pathway (Ouyang et al, 2017;Law et al, 2017;Han et al, 2017;Ha et al, 2017;Shiloh et al, 2018) (mechanism 1 in Fig. 2).…”
Section: Death From Autosismentioning
confidence: 99%
“…It was also reported that luteolin, a flavone type of flavonoid, exerted antitumor effects via autophagy, cell cycle arrest, and apoptosis in SMMC-7721 cells [109]. A flavonol type of flavonoid, kaempferol, inhibited the proliferation of HCC cell lines and primary human HCC cells via the induction of autophagy and apoptosis by AMPK activation [81]. Kaempferol treatment resulted in the inactivation of mTORC1 signaling, which was restored by AMPK inhibition with either small hairpin RNA (shRNA) for AMPKα1 or dominant negative mutation.…”
Section: Autophagic Cell Death By Small Moleculesmentioning
confidence: 97%